The content of mercury (Hg) in oilfish (Ruvettus pretiosus) and escolar (Lepidocybium flavobrunneum) in the fish processing units in Jakarta and Bitung, Indonesia - Samad, Sulthana; Berhimpon, S; Montolalu, Roike I; Lasut, Markus T (Universitas Sam Ratulangi, 2014)
Research on the mercury (Hg) content in oilfish (Ruvettus pretiosus) and escolar (Lepidocybium flavobrunneum) has been carried out, which aims to examine and assess the quality of the fish based on Hg content. Measurement of Hg performed using the analysis procedures in accordance with the Indonesian National Standard (SNI 01-2354-2006). The results showed that Hg measured in all fish samples in which its amount varies based on the size and place, and is influenced by the size (weight) of the sample. Furthermore, it can be concluded that the smaller the size of the fish sampled, then the lower the content of Hg, and the size (weight) >11 kg, the two types of fish that have bad quality where it is not safe for consumption, because it contains Hg higher than the safety limit set by the Government of Indonesia (0.5 ppm).Â Penelitian tentang kandungan merkuri (Hg) pada ikan oilfish (Ruvettus pretiosus) dan escolar (Lepidocybium flavobrunneum) telah dilakukan, yang bertujuan untuk menelaah dan menilai mutu kedua jenis ikan tersebut terhadap kandungan Hg. Pengukuran Hg dilakukan menggunakan prosedur analisis sesuai dengan Standar Nasional Indonesia (SNI 01-2354-2006). Hasil penelitian menunjukkan bahwa Hg terukur pada semua sampel ikan di mana jumlahnya bervariasi berdasarkan ukuran dan tempat, serta dipengaruhi oleh ukuran (berat) sampel. Selanjutnya dapat disimpulkan bahwa semakin kecil ukuran ikan sampel, maka makin rendah kandungan Hg, dan pada ukuran (berat) >11 kg, kedua jenis ikan tersebut memiliki mutu yang tidak baik di mana tidak aman untuk dikonsumsi, karena memiliki kandungan Hg lebih tinggi dari batas aman yang ditetapkan oleh Pemerintah Indonesia (0,5 ppm).